Fabricating poly(methyl methacrylate) parts using high-speed sintering. (January 2020) - Bharaj, Karan; Paul, Sourabh; Mumtaz, Kamran Aamir; Chisholm, Michael; Hopkinson, Neil
The ability of high-speed sintering to fabricate fully functional polymer parts at higher production rates as compared to other alternative additive manufacturing processes makes it prudent to further investigate its capability in processing different materials. The preferential deposition of a radiation absorbing material, which is often presented in the form of a liquid ink, on the powder bed can be considered the highlight of this technology. The effect of 'print density', that is, the amount of ink which is deposited, on the mechanical properties of parts made of an amorphous polymer, poly(methyl methacrylate), was investigated along with its potential role in controlling the porosity and partial melting. The ultimate tensile strength was measured and compared to other additive manufacturing technologies such as laser sintering and was found to be comparable, possibly due to the gradual supply of heat from the infrared lamp which allowed the amorphous poly(methyl methacrylate) particles to melt and have proper bonding with neighbouring particles as compared to the fast lasing action in laser sintering, where the sudden introduction and the withdrawal of the heat source (laser) led to poor inter-particle bonding.